Effect of Replacement of Cotton Seed Cake and Wheat Bran by Formaldehyde Treated Mustard Cake and Bakery Waste on Blood Constituents in Lambs - Ganai, A M; Purohit, G R; Mathur, B K (Annals of Arid Zone, 2016)
An experiment was conducted on sixteen male healthy Nali lambs of 7-8 months of age and of uniform conformation and weight, divided randomly into 4 equal groups and were fed four different isonitrogenous rations, viz., TI [cotton seed cake (CSC) 38; wheatbran (WB) 22; barley 23; guarkorma 12; jaggery 3; salt I; min. mix. I], T2 [CSC replaced by deoiled mustard cake (DMC) on protein basis], T3 [DMC treated with 1% formaldehyde (HCHO)] and T4 [HCHO treated DMC; WB replaced by bakery waste (BW) on protein basis] for a period of 120 days along with sewan (Lasiurus sindicus) hay as basal roughage. Haematological studies were conducted’ in the beginning and thereafter at monthly interval. The blood parameters studied were haemoglobin, packed cell volume, blood glucose, blood urea, total serum proteins, serum albumin and serum globulin. All the parameters were found to be in normal range. No significant effect of the treatments was observed on Hb, PCV, blood glucose, total serum proteins, serum albumin and serum globulin. Significant effect due to treatment was observed on blood urea. The results showed that treatment of DMC with 1% HCHO and replacement of WB by BW in the ration of sheep is safe for optimum biological response.